2015
DOI: 10.1016/j.anireprosci.2015.05.013
|View full text |Cite
|
Sign up to set email alerts
|

The role of RFamide-related peptide 3 (RFRP3) in regulation of the neuroendocrine reproductive and growth axes of the boar

Abstract: a b s t r a c tRFamide-related peptide 3 (RFRP3) has been implicated in regulating reproduction and growth. This regulation appears to be dependent upon sex, species, physiological status, and developmental stage. The objective of the present study was to evaluate the effects of RFRP3 on circulating concentrations of luteinizing hormone (LH) and growth hormone (GH) in mature boars. The hypothesis was RFRP3 would reduce circulating concentrations of LH and increase concentrations of GH. Meishan boars (716.6 ± 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…256 However, further studies in rodents, ewes, pigs and horses did not yield any support for a hypophysiotropic effect of RFRP-3. 218,236,245,248,257 Furthermore, although RFRP-3 is detected in the ewe portal blood, its circulating levels show no correlation with LH levels in the peripheral blood. 258 Importantly, ablation of the NpffR2 gene does not compromise mice fertility, although several minor to moderate effects were reported.…”
Section: A Disputed Role Of Rfrp-3 In the Seasonal Regulation Of Bree...mentioning
confidence: 94%
“…256 However, further studies in rodents, ewes, pigs and horses did not yield any support for a hypophysiotropic effect of RFRP-3. 218,236,245,248,257 Furthermore, although RFRP-3 is detected in the ewe portal blood, its circulating levels show no correlation with LH levels in the peripheral blood. 258 Importantly, ablation of the NpffR2 gene does not compromise mice fertility, although several minor to moderate effects were reported.…”
Section: A Disputed Role Of Rfrp-3 In the Seasonal Regulation Of Bree...mentioning
confidence: 94%
“…These findings suggest the role of RFRP-3 to suppress HPG axis before puberty. Johnson and Fraley [ 69 ] reported that there are no alterations in the pubertal onset in RFRP-3 and GPR 147 knocked down models. Lima et al .…”
Section: Functions Of Rfrp-3 In Reproductionmentioning
confidence: 99%
“…When RFRP-3 was largely infused into the peripheral circulation of OVX gilts, LH secretion remained unchanged, unless very high doses were given. It also took large pharmacological doses of RFRP-3 to impact the pulsatile secretion of LH in intact mature boars ( Thorson et al, 2015 ). As noted, the porcine RFRP preproprotein can yield an RFRP-2 peptide that ruminants and rodents do not produce ( Yoshida et al, 2003 ).…”
Section: Neuropeptide Modulators Of Gnrh Neuronal Activity Gnrh Secretion and Reproduction That Act Directly On Gnrh Neuronsmentioning
confidence: 99%